Nucleotide- and protein-dependent functions of the mammalian cytoplasmic actins - Sundby, Lauren (My University, 2022)
The mammalian cytoplasmic β- and γ-actin proteins are 99% identical but carry out unique biological functions. Essential functions of β-actin have been linked to protein-independent functions of the Actb nucleotide sequence rather than the protein. I generated a novel mouse line to determine if the γ-actin gene, Actg1, also supports protein-independent functions. Mice with a knocked out (KO) Actg1 gene expressing γ-actin from Actb were viable but had increased mortality despite expressing γ-actin protein at levels no different than control cells with normal survival. A survival defect in Actg1 KO mice expressing a constant level of γ-actin protein revealed an important role for the Actg1 nucleotide sequence. Cells isolated from these mice had normal proliferation rates while Actg1 KO cells devoid of γ-actin have impaired proliferation, suggesting a role for the γ-actin protein in cell growth. Together, these data identified unique roles for the Actg1 nucleotide sequence and γ-actin protein.Actb KO mice are embryonic lethal and Actb KO cells fail to proliferate. In contrast, mice and cells specifically lacking β-actin protein are viable with normal survival and normal proliferation, respectively. To determine why the Actb nucleotide sequence is essential for organism development and cell function I used RNA-sequencing and mass spectrometry to analyze the transcriptome, proteome, and phosphoproteome of Actb KO cells. I observed large scale changes in transcription, translation, and protein- phosphorylation in Actb KO cells, suggesting an important role for Actb in gene expression and protein modification. Analysis of differentially expressed transcripts and proteins in Actb KO cells identified the cell cycle as a significantly dysregulated pathway, implicating Actb as an important regulator of the cell cycle.
University of Minnesota Ph.D. dissertation. December 2022. Major: Molecular, Cellular, Developmental Biology and Genetics. Advisor: James Ervasti. 1 computer file (PDF); vii, 128 pages.
Keywords: Actb; Actg1; actin; actin isoforms; β-actin; γ-actin